If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 10x + -16 Reorder the terms: -6 + 5x = 10x + -16 Reorder the terms: -6 + 5x = -16 + 10x Solving -6 + 5x = -16 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -6 + 5x + -10x = -16 + 10x + -10x Combine like terms: 5x + -10x = -5x -6 + -5x = -16 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 + -5x = -16 + 0 -6 + -5x = -16 Add '6' to each side of the equation. -6 + 6 + -5x = -16 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = -16 + 6 -5x = -16 + 6 Combine like terms: -16 + 6 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 2x+36=12x-74 | | 7x-9=4x+12 | | =(6z^9-5z^4+4z^2+6)+(7z^7+4z^4-6z) | | 5x+7=77-7x | | 7x-2x=12 | | 3u+20=8u | | 6x+13=-9-10 | | 7g-15=g-3 | | 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 | | -104-7x=10x+15 | | 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 |